2011
DOI: 10.4314/wajm.v30i1.69882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Government-Community Healthcare Co-Financing on Maternal and Child Healthcare in Nigeria

Abstract: BACKGROUND: Effective maternal and child healthcare delivery requires a proper and adequate funding of the health sector. OBJECTIVE: To determine the effect of government-community healthcare co-financing on maternal and child healthcare services' delivery. METHODS: A descriptive, cross-sectional study with an intervention component, conducted amongst 240 women from Igboukwu (intervention area), and Ekwuluobia (control area), of Anambra State of Nigeria. RESULTS: The biosocial characteristics of the respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…A voucher system that catered for costs for ANC services and hospital delivery in Uganda raised demand for facility-based deliveries by 52.3 %, of which about 9 % were new health facility users [ 39 ]. In Nigeria, a co-financing program for maternal health between the government and the community resulted in a 60 percentage point increase in the utilization of maternal health services (from 26.7 to 85.6 %) [ 40 ], while a user fee exemption program in the same country resulted in increased uptake of institutional deliveries by up to 88 %, resulting in a decline in institutional MMR from 532 to 371 per 100,000 live births [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A voucher system that catered for costs for ANC services and hospital delivery in Uganda raised demand for facility-based deliveries by 52.3 %, of which about 9 % were new health facility users [ 39 ]. In Nigeria, a co-financing program for maternal health between the government and the community resulted in a 60 percentage point increase in the utilization of maternal health services (from 26.7 to 85.6 %) [ 40 ], while a user fee exemption program in the same country resulted in increased uptake of institutional deliveries by up to 88 %, resulting in a decline in institutional MMR from 532 to 371 per 100,000 live births [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Obare et al 2014 [ 35 ]; (level V); 8. Adinma et al 2011 [ 40 ]; (level V); 9. Ezugwu et al 2011 [ 41 ]; (level III); 10.…”
Section: Methodsmentioning
confidence: 99%
“…These funds are used either to meet the medical (drugs, supplies, consultation fees) or nonmedical costs (transport, food etc.) of health care and have been successful in increasing the utilization of MNH services [13, 14, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…In a previous study conducted in Anambra State, researchers found a massive increase in utilization of other maternal and child healthcare services except immunization services at primary health care centers in their study communities. [23] There was no clear reason for this but the authors opined that too frequent SIAs might have diverted some mothers' attention from routine immunization. [23] Community-engaged research approach using focus group discussions and other qualitative research methodologies may yield valuable information.…”
Section: Decentralization Of the Cold-chain Maintenance To Thementioning
confidence: 99%
“…[23] There was no clear reason for this but the authors opined that too frequent SIAs might have diverted some mothers' attention from routine immunization. [23] Community-engaged research approach using focus group discussions and other qualitative research methodologies may yield valuable information. Local managers and health workers could also provide new insights into the problem.…”
Section: Decentralization Of the Cold-chain Maintenance To Thementioning
confidence: 99%